Prevalence and distribution of soil-transmitted helminth infections in India - Nasir Salam; Saud Azam (BMC, 2017)
Abstract Background Understanding the prevalence of soil-transmitted helminth infections is necessary to plan control strategies and focus on highly endemic regions for preventive chemotherapy and improved sanitation facilities. India is known to be endemic for soil-transmitted helminth infections. Methods To understand the prevalence, spatial distribution and identify high-risk zones, a systematic search of published literature was carried out based on PRISMA guidelines from the year 2000 to 2015. Results A careful screening of the identified literature yielded 39 studies that reported the prevalence of soil-transmitted helminth infections from 19 different states of India. Ascaris lumbricoides was the most prevalent parasite. Higher than 50% prevalence was reported from six states. Nearly 90% studies reported the prevalence of more than one parasite species in the same sample population. Conclusion This is the first study to comprehensively review the literature associated with soil-transmitted helminth infections from India giving a clear idea of its prevalence, distribution and high endemic areas.